2019
DOI: 10.1039/c9nj02092f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, DFT calculations and anticancer activity of a new oxidovanadium(iv) complex with a ligand derived from o-vanillin and thiophene

Abstract: New vanadium complex was synthesized and fully characterized showing promising anticancer activity on triple negative breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Finally, our previous results on an oxidovanadium(IV) complex with other thiophenes containing Schiff base ligands, showing a much higher IC 50 value on MG-63 cells than CuHL, demonstrate the importance of the nature and the environment geometry of the metal center in the effectiveness of metallo-drugs [54].…”
Section: Cell Viability Studymentioning
confidence: 66%
See 1 more Smart Citation
“…Finally, our previous results on an oxidovanadium(IV) complex with other thiophenes containing Schiff base ligands, showing a much higher IC 50 value on MG-63 cells than CuHL, demonstrate the importance of the nature and the environment geometry of the metal center in the effectiveness of metallo-drugs [54].…”
Section: Cell Viability Studymentioning
confidence: 66%
“…than CuHL, demonstrate the importance of the nature and the environment geometry of the metal center in the effectiveness of metallo-drugs [54].…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…These findings are in good agreement with the previous studies which showed the high cytotoxic activity of thiophene derivatives against cancer cells. [ 36,70 ] In addition, α‐tpys (2,2′:6′,2″‐tpy) and their derivatives displayed stronger cytotoxicity against A‐498, PC‐3, and HT‐29 cancer cell lines than doxorubicin. The furyl and thienyl analogs were more cytotoxic than the corresponding phenyl analog.…”
Section: Resultsmentioning
confidence: 99%
“…[172,173] Recent studies in MDA-MB-231 cells have shown apoptotic and autophagic cell death with notch pathway inhibition of a vanadium-based complex, compound 58, a oxidovanadium (IV) complex by Gonzalez-Baró and co-workers with a chelating ligand made from the condensation reaction of o-vanillin and 2thiophenemethylamine. [174] Cellular studies in MDA-MB-231 cells showed cytotoxicity (IC 50 = 29 � 1.7 μM, 48 h), an apoptotic cell death, antimigratory activity, and increased ROS production. [174]…”
Section: Vanadium Compoundsmentioning
confidence: 95%
“…[174] Cellular studies in MDA-MB-231 cells showed cytotoxicity (IC 50 = 29 � 1.7 μM, 48 h), an apoptotic cell death, antimigratory activity, and increased ROS production. [174]…”
Section: Vanadium Compoundsmentioning
confidence: 95%